Lattice Dynamics and Transport Properties of Multiferroic DyMn2O5 - Javed Ahmad; Syed Hamad Bukhari; M. Tufiq Jamil; Mehr Khalid Rehmani; Hammad Ahmad; Tahir Sultan (Advances in Condensed Matter Physics, 2017)
We have investigated the optical and electrical properties of polycrystalline DyMn2O5 synthesized by sol-gel method. Analysis of the reflectivity spectrum has led to the observation of 18 infrared (IR) active phonon modes out of 36 predicted ones. We discuss the results in terms of different phonon bands originated as a result of atomic vibrations. Moreover, the optical energy band gap of Eg(OC)~1.78 eV has been estimated from optical conductivity (σ1(ω)) spectrum. The energy band gap and optical transitions were also determined from UV-visible absorption spectrum and band gap of Eg(UV)~1.57 eV was estimated. Moreover, DC electrical resistivity shows the p-type polaronic conduction above room temperature.